2008
DOI: 10.1158/1055-9965.epi-07-0750
|View full text |Cite
|
Sign up to set email alerts
|

Family History of Cancer and Associated Risk of Developing Neuroendocrine Tumors: A Case-Control Study

Abstract: Background: Carcinoids are rare neuroendocrine tumors (NET). Familial clusterings of NETs are rarely reported, except for a small proportion associated with multiple endocrine neoplasia syndrome type 1. We evaluated the effect of positive family history of NET as well as other cancers on the development of NETs arising at five different locations. Methods: We conducted a retrospective, hospital-based, case-control study involving 740 patients with histologically confirmed NETs and 924 healthy controls. Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 30 publications
3
58
1
1
Order By: Relevance
“…A family history of cancer appears to be a strong risk factor for development of all types of carcinoids. Ileal carcinoids have been found to be strongly associated with cancers of the gastrointestinal tract and prostate [27]. These data are in line with reports of increased numbers of malignancies in patients with carcinoid disease [18,19,28].…”
Section: Profiling Of Susceptibility Genes For Ileal Carcinoidssupporting
confidence: 81%
“…A family history of cancer appears to be a strong risk factor for development of all types of carcinoids. Ileal carcinoids have been found to be strongly associated with cancers of the gastrointestinal tract and prostate [27]. These data are in line with reports of increased numbers of malignancies in patients with carcinoid disease [18,19,28].…”
Section: Profiling Of Susceptibility Genes For Ileal Carcinoidssupporting
confidence: 81%
“…Also, a recent case-control study found an increased risk of developing small bowel carcinoids in individuals with a family history of other cancers, in particular colorectal and prostate cancer [15]. …”
Section: Discussionmentioning
confidence: 99%
“…insular, trabecular, glandular, and diffuse growth patterns, respectively. In addition, the recently added ‘solid’ variant was applied [15]. The histopathological and IHC subdivision of the carcinoids with respect to their degree of malignancy followed the WHO classification, i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Выполнение лимф-аденэктомии достоверно улучшает общую выживаемость. Адекватным объемом лимфо-диссекции при НЭО тонкой кишки, по мне-нию некоторых авторов, необходимо считать удаление как минимум 8 лимфатических узлов [64][65][66][67][68][69][70][71][72][73][74][75][76].…”
Section: хирургическое лечениеunclassified